State Capacity Building and Government-Citizens Relationship Patterns: a Sub National Analysis in Mexico - Hevia, Felipe J. (Revista del CLAD Reforma y Democracia, 2015)
State capacities, defined as the capacities of the state to develop and implement strategies to achieve economic and social goals in society, it is important to analyze design and implementation of public policies in several fields. They are also part of the research agenda in Mexico. Most of the literature has focused on the analysis of the technical and administrative capacities, leaving less studied relational capacities, ie, those that relate to the relationship of the state with the socioeconomic environment, in particular the relationships established leaders and citizens. Using the case of the educational field in Veracruz, the objective is to analyze the types of relational capabilities in a local government building in Mexico, seeking to identify relationship patterns that allow to analyze state capacities. Methodology: we opted for a perspective of “political anthropology” that could analyze recurring patterns of relationship between society and government. First, types of relationship patterns were constructed, and secondly, we identify and analyze the criteria for understanding these patterns in terms of their effects on state capacity. Results: particularistic, contentious and disruptive-regulated participation ratios: three patterns of relationship were identified. The first used a huge range of systems and direct citizen service requests, the latter are characterized by street protests and the third by the use of institutional participation bodies. Shape and type of relationship: two analytical classification criteria were identified. Discussion: relationship types, appealing to favor or to the right, and types of relationships, institutional or otherwise, will allow us to understand how to build a differentiated response capacity of government that favors relationships, but inefficient particularistic relationship.